2011
DOI: 10.5505/jkartaltr.2011.18199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intratympanic steroid treatment versus hemodilution and vasoactive treatment combination in sudden hearing loss

Abstract: ÖzetAmaç: Ani işitme kaybı ardışık 3 veya daha fazla frekansta en az 30 dB kaybın olduğu son 3 gün içinde ortaya çıkmış sensörinöral işitme kaybı olarak tanımlanabilir. Bu çalışma-daki amacımız, intratimpanik steroid tedavisi ile hemodilüs-yon ve vazoaktif kombinasyon tedavisinin etkinliklerini karşılaştırmaktır. Gereç ve Yöntem:Bu prospektif çalışmaya, 2005 ile 2010 yıl-ları arasında kliniğimize ani işitme kaybı şikayeti ile başvu-ran 49 hasta dahil edildi. Bu hastalardan 25'i intratimpanik steroid grubuna, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Aydın et al reported that IT-MP had better hearing results compared to combined therapy (intravenous dextran and oral pentoxyfilline). 24 They administered 5 intratympanic injections regardless of the hearing results. We took PTA into consideration for deciding to continue the injections.…”
Section: Discussionmentioning
confidence: 99%
“…Aydın et al reported that IT-MP had better hearing results compared to combined therapy (intravenous dextran and oral pentoxyfilline). 24 They administered 5 intratympanic injections regardless of the hearing results. We took PTA into consideration for deciding to continue the injections.…”
Section: Discussionmentioning
confidence: 99%